2018
DOI: 10.1007/s11886-018-0943-5
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibitors and Mechanisms of Hypertension

Abstract: Inhibition of SGLT2 in the renal proximal tubule results in increased urinary glucose excretion and modest improvements of hemoglobin A1C. Treatment with any of the three currently FDA-approved SGLT2 inhibitors (canagliflozin, dapagliflozin, empagliflozin) results in sustained systolic and diastolic blood pressure reduction, in part via minimal natriuresis and possible reductions in sympathetic tone. Recent randomized clinical trials in high cardiovascular risk patients with type 2 diabetes suggest that the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 53 publications
2
36
0
1
Order By: Relevance
“…Scattered reports suggested that there might be a risk for acute kidney injury (AKI) with the use of SGLT2is, which might occasionally require renal replacement therapy 219,220 . Several mechanisms have been proposed to explain a risk of AKI with SGLT2is ( Supplementary Box 1).…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Scattered reports suggested that there might be a risk for acute kidney injury (AKI) with the use of SGLT2is, which might occasionally require renal replacement therapy 219,220 . Several mechanisms have been proposed to explain a risk of AKI with SGLT2is ( Supplementary Box 1).…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…It turns out that SGLT-2 inhibitors reduce systolic and diastolic pressure. It is believed that these drugs reduce sympathetic tension, increase osmotic diuresis and minimally increase natriuresis [41,42]. Such action additionally reduces the risk of cardiovascular events [43].…”
Section: Current Status and Future Perspectivementioning
confidence: 99%
“…In patients with type 2 diabetes, renal glucose transport thresholds are increased as compared to normal individuals as a result of SGLT2 upregulation. The intrinsic risk of hypoglycemia with SGLT2 inhibitors is expected to be low, because this effect is insulin independent, and the amount of urinary glucose excretion is determined in part by blood glucose concentrations [136][137][138][139].…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%